Screening art : modernist aesthetics and the socialist imaginary in East German cinema - Allan, Seán (Film Europa, 2019)
With internationalist aspirations and wide-ranging historical perspectives, East German films about artists and their work became hotly contested spaces in which filmmakers could look beyond the GDR and debate the impact of contemporary cultural policy on the reception of their pre-war cultural heritage. Spanning newsreels, documentaries, and feature films, Screening Art is the first full-length investigation into a genre that has been largely overlooked in studies of DEFA, the state-owned Eastern German film studio. As it shows, 'artist-films' played an essential role in the development of new paradigms of socialist art in postwar Europe.